การกำจัดสีน้ำทิ้งจากอุตสาหกรรมฟอกย้อมสิ่งทอ โดยกระบวนการตกตะกอนทางเคมีด้วยโพลีเมอร์ : รายงานผลการวิจัย - นภา ศิวรังสรรค์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objective of this experiment was to to evaluate the color removal efficeincy from dye solution prepared in the laboratory by chemical coagulation with 2 cationic polymers (Lamflco 2515 and Zentrifloc 95). Alum was used as coagulant to compare the color removal efficiency from textile effluent collected from sites with cationic polymer together with anionic polymer (Lamfloc 7985). In thsi study 2 kinds of dyestuff, reactive and vat, and 2 tones, yellow and blue. It was found that Lamfloc 1525 is more efficient than Zentrifloc 95. For removing color from textile effluent, Lamfloc 7985 has little enhancement when used with Lamfloc 1525 and Lamfloc 1525 is more effiient than alum. The efficiency of Lamfloc 1525 is about 90%.